EBI metagenomics in 2016 - an expanding and evolving resource for the analysis and archiving of metagenomic data. Issue Volume 44:Issue D1(2016) (17th November 2015) - Mitchell, Alex; Bucchini, Francois; Cochrane, Guy; Denise, Hubert; Hoopen, Petra ten; Fraser, Matthew; Pesseat, Sebastien; Potter, Simon; Scheremetjew, Maxim; Sterk, Peter; Finn, Robert D.
Abstract: EBI metagenomics (https://www.ebi.ac.uk/metagenomics/ ) is a freely available hub for the analysis and archiving of metagenomic and metatranscriptomic data. Over the last 2 years, the resource has undergone rapid growth, with an increase of over five-fold in the number of processed samples and consequently represents one of the largest resources of analysed shotgun metagenomes. Here, we report the status of the resource in 2016 and give an overview of new developments. In particular, we describe updates to data content, a complete overhaul of the analysis pipeline, streamlining of data presentation via the website and the development of a new web based tool to compare functional analyses of sequence runs within a study. We also highlight two of the higher profile projects that have been analysed using the resource in the last year: the oceanographic projects Ocean Sampling Day and Tara Oceans.